PENGARUH KEAMANAN, KEMUDAHAN PENGGUNAAN DAN E-SERVICE QUALITY TERHADAP LOYALITAS KONSUMEN PENGGUNA SHOPEEPAY PADA MAHASISWA FEB UNIVERSITAS WIJAYA KUSUMA SURABAYA - Maulidanty, Aprilia; Giyana (GEMAH RIPAH: Jurnal Bisnis, 2025)
The rapid growth of digital wallets has increased the use of Shopeepay among university student, making user loyalty a critical issue in the fintech industry. This study aims to analyze the effect of security, ease of use, and e-service quality on customer loyalty of Shopeepay users among students of the Faculty of Economics and Business at Wijaya Kusuma University Surabaya. This research employed a quantitative method with an explanatory survey approach. Data were collected from 100 respondents selected through purposive sampling and analyzed using multiple linear regression. The results indicate that security and ease of use do not have a significant effect on customer loyalty, while e-service quality has a positive and significant effect. Simultaneously, security, ease of use and e-service quality significantly influence customer loyalty. This study concludes that e-service quality is the primary determinant of student loyalty in using digital wallet services. The findings imply that improving system reliability, transaction efficiency, and customer service responsiveness is essential for sustaining user loyalty amid intense competition in the fintech industry.